Correlation between CT findings and thoracoscopic diagnosis in diffuse pleural disease - Piacibello, Edoardo; Cardinale, Luciano; Righi, Luisella; Sverzellati, Nicola; Ardissone, Francesco; Veltri, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Objective: Computed Tomography (CT) is considered part of the routine diagnostic workup for pleural malignancy. The definitive diagnosis of pleural malignancy depends upon histological confirmation by pleural biopsy. The aim of this study is to assess the sensitivity and specificity of CT, in view of the latest imaging technologies, in detecting pleural malignancy compared to definitive histology achieved via thoracoscopy (VATS). Materials and methods: We included in this retrospective study 90 patients (36 F, 54 M) with suspected pleural malignancy evaluated in our Institution with CT scan who received a definitive diagnosis after VATS biopsy. Unaware of histopathologic diagnoses CT scans were evaluated by a junior and two experts thoracic radiologist. Conclusions were reached by consensus. Results: We evaluated all CT signs suggestive for malignant pleural diseases: pleural thickening > 10 mm (Se 0,41 , Sp 0,79); nodular thickening (Se 0,86, Sp 0,75); circumferential thickening (Se 0,79, Sp 0,69); irregular pleural thickening (Se 0,77, Sp 0,91); mediastinal involvement (Se 0,88, Sp 0,64); costal involvement (Se 0,89, Sp 0,60); diaphragmatic involvement (Se 0,88, Sp 0,53). Furthermore, the diagnostic performance of additional CT features was evaluated: concomitant costal, mediastinal and diaphragmatic pleura lesions (Se 0,84, Sp 0,69); nodular/irregular thickening with mediastinal pleural involvement (Se 0,83, Sp 0,90); nodular/irregular thickening with diaphragmatic pleural involvement (Se 0,81, Sp 0,90). Conclusions: CT confirms its central role in the pleura malignancy. The high sensibility, respect to previous studies, especially in the presence of nodular pleural thickening, may lead to reconsider at least partly the diagnostic pathway of diffuse pleural disease, avoiding the use of VATS in patients not eligible for surgery, in favor of US or CT guided core biopsy.